An investigation on consumer’s behaviors towards well-known luxury brands - Mohammad Javad Ghasemi (Management Science Letters)
This paper presents an empirical investigation to find the relationship between consumer’s behaviors towards well-known luxury brands in Iranian market. The study designs a questionnaire in Likert scale and distributes it among 250 randomly people who purchase luxury products. The study investigates the effects of three variables including perception value, social normality and need for being exclusive on perception of a brand for motivating customers to purchase luxury products. In addition, the study tries to find out whether customers’ educational backgrounds influence on purchasing luxury products or not. Cronbach alphas are all well above the minimum acceptable level, which validates the survey. Using structural equation modeling, the study confirms all hypotheses of the survey.